Chimie des substances naturelles et pharmacie : à la croisée des chemins - Beniddir, Mehdi A.; Poupon, Erwan (Comptes Rendus. Chimie, 2024)
Past, present, future ... An overview of the importance of natural products in pharmacy and drug discovery is provided herein. This “account” article seeks to shed light on current issues and challenges, through a critical analysis ranging from bioprospecting to the marketing of new drugs.